A new correction method serving to eliminate the parabola effect of flatbed scanners used in radiochromic film dosimetry. Issue 2 (13th January 2014) - Poppinga, D.; Schoenfeld, A. A.; Doerner, K. J.; Blanck, O.; Harder, D.; Poppe, B.
Abstract : Purpose: : The purpose of this study is the correction of the lateral scanner artifact, i.e., the effect that, on a large homogeneously exposed EBT3 film, a flatbed scanner measures different optical densities at different positions along the x axis, the axis parallel to the elongated light source. At constant dose, the measured optical densitiy profiles along this axis have a parabolic shape with significant dose dependent curvature. Therefore, the effect is shortly called the parabola effect. The objective of the algorithm developed in this study is to correct for the parabola effect. Any optical density measured at given position x is transformed into the equivalent optical density c at the apex of the parabola and then converted into the corresponding dose via the calibration of c versus dose. Methods: : For the present study EBT3 films and an Epson 10000XL scanner including transparency unit were used for the analysis of the parabola effect. The films were irradiated with 6 MV photons from an Elekta Synergy accelerator in a RW3 slab phantom. In order to quantify the effect, ten film pieces with doses graded from 0 to 20.9 Gy were sequentially scanned at eight positions along the x axis and at six positions along the z axis (the movement direction of the light source) both for the portrait and landscape film orientations. In order to test the effectiveness of the new correction algorithm, the dose profiles of an open square field and an IMRT plan were measured by EBT3 films and compared with ionization chamber and ionization chamber array measurement. Results: : The parabola effect has been numerically studied over the whole measuring field of the Epson 10000XL scanner for doses up to 20.9 Gy and for both film orientations. The presented algorithm transforms any optical density at position x into the equivalent optical density that would be measured at the same dose at the apex of the parabola. This correction method has been validated up to doses of 5.2 Gy all over the scanner bed with 2D dose distributions of an open square photon field and an IMRT distribution. Conclusions: : The algorithm presented in this study quantifies and corrects the parabola effect of EBT3 films scanned in commonly used commercial flatbed scanners at doses up to 5.2 Gy. It is easy to implement, and no additional work steps are necessary in daily routine film dosimetry.